Glyoxal as an alternative fixative to formaldehyde in immunostaining and super‐resolution microscopy. (16th November 2017) - Richter, Katharina N; Revelo, Natalia H; Seitz, Katharina J; Helm, Martin S; Sarkar, Deblina; Saleeb, Rebecca S; D'Este, Elisa; Eberle, Jessica; Wagner, Eva; Vogl, Christian; Lazaro, Diana F; Richter, Frank; et al.
Abstract: Paraformaldehyde (PFA) is the most commonly used fixative for immunostaining of cells, but has been associated with various problems, ranging from loss of antigenicity to changes in morphology during fixation. We show here that the small dialdehyde glyoxal can successfully replace PFA. Despite being less toxic than PFA, and, as most aldehydes, likely usable as a fixative, glyoxal has not yet been systematically tried in modern fluorescence microscopy. Here, we tested and optimized glyoxal fixation and surprisingly found it to be more efficient than PFA‐based protocols. Glyoxal acted faster than PFA, cross‐linked proteins more effectively, and improved the preservation of cellular morphology. We validated glyoxal fixation in multiple laboratories against different PFA‐based protocols and confirmed that it enabled better immunostainings for a majority of the targets. Our data therefore support that glyoxal can be a valuable alternative to PFA for immunostaining. Synopsis: Enhanced fixation speed, decreased toxicity and better preservation of cytosolic nanostructures and membrane‐bound antigens make the small dialdehyde glyoxal a promising alternative to the commonly used paraformaldehyde (PFA), in particular for super‐resolution microscopy. Glyoxal penetrates cells faster than conventional solutions of PFA. Glyoxal fixes and retains more cellular proteins and RNA than PFA. Immunostaining of glyoxal‐fixed samples reveals higher amounts of target proteins, and typically results in brighter microscopy images. Glyoxal fixation was validated against multiple PFA‐based protocols in several laboratories. Abstract : Enhanced fixation speed and better preservation of cytosolic nanostructures and membrane‐bound antigens make the small dialdehyde glyoxal a promising substitute for the commonly used paraformaldehyde.